2021
DOI: 10.1080/03057925.2020.1868976
|View full text |Cite
|
Sign up to set email alerts
|

Gendering childhood(s) and engagement with schooling in rural Sierra Leone

Abstract: In spite of widespread initiatives to improve access to education for girls, substantive concerns remain. While there is a rich and growing body of literature on gendered experiences of school in majority world contexts, absent is a focus on how this intersects with children's out of school lives. Further, research with children in rural communities is limited, including those who are in the earlier years of their schooling. This paper addresses these gaps, focusing on gendered dynamics in the everyday lives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Our results indicate that children in primary schools in Sierra Leone are exposed to significant levels of direct violence (physical and psychological) perpetrated by their teachers and colleagues. This confirms several previous studies that showed high levels of violence against children in Sierra Leone (UNICEF, 2008; Concern Worldwide et al , 2010; UNICEF, 2010; Devine et al , 2019; Zuilkowski et al , 2019). Apart from direct violence, the composite index proposed also assesses the level of structural and cultural violence that children experience in schools and their lives in general.…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that children in primary schools in Sierra Leone are exposed to significant levels of direct violence (physical and psychological) perpetrated by their teachers and colleagues. This confirms several previous studies that showed high levels of violence against children in Sierra Leone (UNICEF, 2008; Concern Worldwide et al , 2010; UNICEF, 2010; Devine et al , 2019; Zuilkowski et al , 2019). Apart from direct violence, the composite index proposed also assesses the level of structural and cultural violence that children experience in schools and their lives in general.…”
Section: Discussionsupporting
confidence: 91%
“…During the discussion of taking this photo, a girl, Isa explained that this is her sister who dropped out from school due to pregnancy and who helps her to study at home. This explanation itself provides rich data and a fertile ground for further exploration of girls’ and women’s everyday life in the community including early pregnancies, barriers for pregnant girls to attend school, as well as about literacy dynamics at home (Devine et al, 2021a, 2021b). But the picture itself also represents a teenager who works (in this case sells small agriculture produce – what can be read from the pan on her head) which tells another story about the incidence of child work, sources of income suitable for women and gendered labour division.
Figure 5.My sister dropped out from school (a photo taken by a girl, Isatu).
…”
Section: Methodsmentioning
confidence: 99%
“…The paper draws on data gathered for a large-scale ongoing research project 'Safe Learning Study'. This longitudinal mixed methods study examines gender relations, literacy, well-being and schooling of primary school children in rural Sierra Leone (Devine et al, 2021). The qualitative component of the study comprises in-depth ethnographic work in four case study communities in a rural Tonkolili district in Northern Sierra Leone.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of intra‐actions is borrowed from Barad's agential realism theory as “mutual constitutions” of subjects and objects (Barad, 2007, p. 33). We argue that concepts of danger and risks are constituted through the intra‐actions that take place between children, adults, material objects, spaces and spiritual beings but also through the intra‐actions with the wider societal context in which children live, including poverty, inequality, gender norms and generational orders (Devine et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation